Developmental milestones and cognitive trajectories in school-aged children with 16p11.2 deletion - Jente Verbesselt; Jeroen Breckpot; Inge Zink; Ann Swillen (Journal of Neurodevelopmental Disorders)
Abstract Background 16p11.2 deletion syndrome (16p11.2DS) is a recurrent CNV that occurs de novo in approximately 70% of cases and confers risk for neurodevelopmental disorders, including intellectual disability (ID) and autism spectrum disorders (ASD). The current study focusses on developmental milestones, cognitive profiles and longitudinal cognitive trajectories. Methods In-person assessments, digital medical records and parental interviews on developmental history of 24 children (5–16 years) with a confirmed BP4-BP5 16p11.2DS were reviewed and analysed for developmental milestones (motor, language, continence). Standardised intelligence tests were administered in all children, and longitudinal IQ-data were available for a subgroup (79%, 19/24). Results Motor, language, and continence milestones were delayed. Average IQ was in the borderline range (IQ 71) with 46% (11/24) having borderline IQ (IQ 70–84). Both intra- and interindividual variability were found across the five cognitive domains with significant discrepancies between verbal and non-verbal skills in 55% (11/20). Longitudinal IQ-data indicate that school-aged children with 16p11.2DS perform statistically significantly lower at the second time point (p < 0.001) with 58% showing a growing into deficit trajectory. Conclusion Delayed motor, language and continence milestones are common in 16p11.2DS carriers. School-aged children with 16p11.2DS show increasing cognitive impairments over time, pointing to the need for early diagnosis, regular cognitive follow-up and individualised intervention. The high prevalence of disharmonic IQ-profiles highlights the importance of expanding the focus beyond full-scale IQ (FSIQ) outcomes. Future studies in larger cohorts including carrier relatives are needed to gain more insight into the penetrance and phenotypic variability of 16p11.2DS.